Medicinal plant knowledge of the Panchase region in the Middle Hills of the Nepalese Himalayas - Bhattarai, K. R.; Måren, I. E.; Chaudhary, R. P. (Banko Janakari, 2013)
Use of plants as medicine has been practiced all over the world since the dawn of human civilisation. In the Himalayas, many medicinal plants yield essential ecosystem services/ benefi ts for the subsistence farmers, many of which grow in the forest ecosystem. However, documentation of traditional medicine and medicinal plants used by local communities is rather poor in Nepal. Panchase forest, Central Nepal, is home of many wild plants, used in traditional medicine, and a livelihood source for many ethnic groups. This study was conducted to document medicinal plant knowledge and plant use in the treatment of different ailments. To explore the ethnobotanical knowledge interviews were conducted with local healers, plant traders and knowledgeable villagers. The study provides information on 45 plant species, belonging to 32 families under 44 genera. The studied medicinal plants were found to be useful for treating 34 different ailments. The study which has 57% resemblance with previous studies. We conclude that a wealth of ethnobotanical knowledge still persists in the Panchase region. However, due to land use change and migration it needs to be preserved for the future through extensive publications and disseminations. DOI: http://dx.doi.org/10.3126/banko.v21i2.9127 Banko Janakari Vol. 21, NO. 2, 2011 Page:31-39 Uploaded date: 10 November, 2013